Temporary left ventricular assistance for extreme postoperative heart failure in two infants with Bland-White-Garland syndrome - Urbańska, Ewa K.; Pawlak, Szymon; Grzybowski, Adam; Śliwka, Joanna; Rycaj, Jarosław; Obersztyn-Zawiślan, Anna; Wierzyk, Arkadiusz; Przybylski, Roman (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Anomalous origin of the left coronary artery from the pulmonary artery (Bland-White-Garland syndrome – BWG) is a serious congenital cardiac anomaly leading to myocardial ischemia with severe heart failure. Immediate surgical correction is the treatment of choice, and the risk of postoperative complications depends on the degree of myocardial injury. The authors present two cases of infants with BWG, in whom long-term (175 and 26 days) left ventricular assistance with a Berlin Heart device was used, resulting in successful weaning from the support and subsequent hospital discharge. Because of serious hemorrhagic complications and their neurological consequences observed in the first patient, the anticoagulation protocol was modified in the second patient, providing more stable support and allowing the device to be removed after a shorter period of time. The Berlin Heart left ventricular assist device may be treated not only as a bridge for transplantation but also, considering the shortage of donors in this age group, as a bridge to recovery.